Digital Leadership in the Age of Transformation: A Global Bibliometric Analysis of Research Trends and Knowledge Structures - Indarta, Yose (PT Mattawang Mediatama Solution, 2025)
This study examines the evolution and future trends of digital leadership through a comprehensive bibliometric analysis of research publications from 2015 to 2024. The investigation employs bibliometric analysis and topic modeling techniques on metadata from 265 Scopus-indexed articles across 199 distinct sources, focusing specifically on publications with